1988
DOI: 10.1159/000124950
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Growth Hormone Releasing Factor and Somatostatin in the Rat Hypothalamus

Abstract: Distribution and staining intensities of growth hormone releasing factor (GRF) and somatostatin (SRIF) were examined in young (3 months of age) and old (24 months of age) male rats of Sprague-Dawley strain, using the PAP immunocytochemical procedure. Some animals of each age group were intraventricularly injected with colchicine to demonstrate immunoreactive neuronal perikarya. GRF-immunoreactive intensities of old rats were markedly reduced in the median eminence as compared with those of young rats. No remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…Age-related changes in these hormone secretions may alter the G H and PRL secretions through the gene expressions. Recently, diminished GHRH secretion, reduced responsiveness to GHRH and enhanced somatostatin release were observed (Sonntag et al, 1983(Sonntag et al, , 1986Morimoto et al, 1988). Functional decline in dopamine (PRL-inhibiting factor, PIF) neurons was also reported in several studies (Simpkins et al, 1977;Gudelsky et al, 1981).…”
Section: Discussionmentioning
confidence: 91%
“…Age-related changes in these hormone secretions may alter the G H and PRL secretions through the gene expressions. Recently, diminished GHRH secretion, reduced responsiveness to GHRH and enhanced somatostatin release were observed (Sonntag et al, 1983(Sonntag et al, , 1986Morimoto et al, 1988). Functional decline in dopamine (PRL-inhibiting factor, PIF) neurons was also reported in several studies (Simpkins et al, 1977;Gudelsky et al, 1981).…”
Section: Discussionmentioning
confidence: 91%
“…In aged mammals, decreased responsiveness to GHRH and reduced GH plasma levels [5, 6, 7, 8] are thought to be responsible for a diminution of muscle mass, an increase of the adipose tissue mass and a deterioration of several tissue and organ functions [8, 9, 10, 11]. In 24-month-old rats, it has been partly related to a decrease in both GHRH hypothalamic content [12, 13] and gene expression [13], but not to a loss of GHRH-containing neurons [12]. The contribution of hypothalamic SRIF to a decreased GH secretion remains however a matter of debate [5, 6, 7, 12, 14, 15, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, GHRH plays a significant role in stimulating the production of somatotropes (21,22). The synthesis and secretion of GHRH in the hypothalamus is thought to be reduced in aged rats fed ad libitum (23,24). There is no direct evidence that GHRH is secreted in aged DR animals in a fashion similar to that observed in young counterparts fed ad libitum However, a recent study reported that pulsatile secretion of GH similar to that in young AL rats is present in aged DR rats, but not in aged AL rats (25), suggesting that GHRH is secreted efficiently in DR rats in later life.…”
Section: Discussionmentioning
confidence: 99%